1991
DOI: 10.1016/s0022-5347(17)38370-2
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Perinephric Hemorrhage: Imaging and Management

Abstract: We report on 10 patients with spontaneous perinephric hemorrhage associated with underlying disease, including renal cell carcinoma (5), angiomyolipoma (2), malignant melanoma (1), periarteritis nodosa (1) and severe portal hypertension (1). The etiology could not be identified with computerized tomography (CT) in 5 cases (50%), including 2 renal cell carcinomas, 1 angiomyolipoma, 1 periarteritis nodosa and 1 portal hypertension. Arteriography demonstrated underlying lesions in 4 of these 5 cases (80%) includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1
6

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 14 publications
1
28
1
6
Order By: Relevance
“…Conversely, one may argue that the patients with such disease can be followed carefully and noninvasively with recurrent radiological studies, such as CT scanning, thus suggesting that aggressive surgical intervention is not justified (14, 30). In our patient, it was difficult to pre-cisely evaluate her for the presence of renal carcinoma by imaging techniques due to the hemorrhagic nature of the kidney (30,31). Therefore, a radical nephrectomy was finally performed despite achieving successful bleeding control by consecutive rounds of renal arterial embolization.…”
Section: Discussionmentioning
confidence: 92%
“…Conversely, one may argue that the patients with such disease can be followed carefully and noninvasively with recurrent radiological studies, such as CT scanning, thus suggesting that aggressive surgical intervention is not justified (14, 30). In our patient, it was difficult to pre-cisely evaluate her for the presence of renal carcinoma by imaging techniques due to the hemorrhagic nature of the kidney (30,31). Therefore, a radical nephrectomy was finally performed despite achieving successful bleeding control by consecutive rounds of renal arterial embolization.…”
Section: Discussionmentioning
confidence: 92%
“…Spontaneous subcapsular or perirenal hemorrhage is a relatively uncommon complication that often requires additional treatment [3,4]. A total of 165 patients with this complication were reported between 1985 and 1999 [5].…”
Section: Discussionmentioning
confidence: 99%
“…A perirenal hematoma can be confused ultrasonographically with a renal tumor or an abscess formation, at which point abdominal CT can be used to confirm the suspected diagnosis. A sizable number of medical studies indicated CT to be more sensitive than USG in making the diagnosis of ScRH [16,17]. In such situations as presence of contrast allergy and pregnancy when CT is considered to be contraindicated, alternative modes of imaging such as magnetic resonance imaging can be implemented.…”
Section: Discussionmentioning
confidence: 99%